Seed enhancements to improve direct-seeding outcomes for native grasses in mine restoration - Berto, Bianca; Ritchie, Alison L.; Erickson, Todd E. (Frontiers in Ecology and Evolution, 2024)
Seed-based restoration in dryland environments is commonly limited by low and sporadic rainfall, extreme temperatures, and degraded soils. These challenges are exacerbated in dryland mine restoration sites where species are seeded onto mine waste substrates due to limited availability of topsoil. Native grasses are focal dryland and mine restoration species, though the ability to deliver seeds to targeted sites presents further constraints to seed-based restoration due to complex seed morphology and site attributes. Seed enhancement technologies (SETs) may help to mitigate environmental stressors and improving seed handling. In this study, SETs which promote seedling recruitment and/or address edaphic challenges while also improving seed morphology and handling were tested in four Australian native grasses (Cymbopogon ambiguus, C. obtectus, Eulalia aurea, and Eriachne obtusa). Flash flaming or acid digestion (depending on species), extruded seed pellets with or without the addition of topsoil, and flaming or acid digestion used in combination with extruded pellets (with or without topsoil) were evaluated on topsoil and mine waste substrates. Material treated with either flash flaming or acid digestion tended to produce similar maximum emergence (week 3), final emergence (week 14), and above-ground biomass (week 14) on both topsoil and mine waste when compared to the un-enhanced (‘control’) treatment. Extruded pellets enhanced emergence (maximum and final) on both soil types, though had no effect on biomass. Extruded pellets containing topsoil and/or when used in combination with flash flamed or acid digested florets, provided the most significant benefits to seedling emergence, particularly on mine waste soil. However, SETs were unable to mitigate the detrimental effects of mine waste substrates on seedling biomass. This study shows promise for improving seed-based restoration in post-mine and dryland environments using SETs, though also highlights potential limitations and the importance of understanding long-term (i.e., beyond emergence) plant recruitment outcomes in SET applications.